Inflammaging: Significance and intervention - Ahmad, Rizwan (International Journal of Health Sciences, 2024)
The year 2000 marked a revolutionary shift in the way we think about aging and longevity, thanks to the groundbreaking work of Professor Franceschi and his colleagues. Their concept of "inflammaging" challenged our entire understanding of the aging process, not just in immunology but across all fields. Through their research, we could recognize the critical role that inflammation plays in the aging of the immune system and its consequences (1). Inflammaging, or inflamm-aging, is an undeniable reality that develops in the human body with advanced age. This low-grade inflammation is an upregulated inflammatory response that can significantly accelerate aging and worsen specific age-related symptoms and diseases. Acknowledging the existence of inflammaging is crucial in tackling the challenges of aging and finding practical solutions to mitigate its adverse effects on our bodies. Inflammaging is when the immune system produces excessive inflammatory cytokines, leading to chronic inflammation. This condition is influenced by various factors such as genetics, environmental factors, and aging.